PROFITABLE CUSTOMER HUNT VIA PROGRAMMING LANGUAGE - Bilge, F. Atil; Cabi, Ayse (European Scientific Journal, ESJ, 2012)
Increase in population results in increase in consumption, and consumption increases the number of customers. Increase in potential customers causes more entrepreneurs taking place in the market and therefore intensifies competition. Increase in the number of potential customers leads to the differentiation of customer needs. At this point, businesses enter a period when they can be successful in competition only if they determine which needs of customers they can meet according to their know-how levels, instead of focusing on every need. At this study, how developments in question put forth the need for profitable customer, how to determine profitable customers and how this can be managed through developing technology, are analyzed.